Conditional performance factors in padel players: a mini review - Guijarro-Herencia, J.; Mainer-Pardos, E.; Gadea-Uribarri, H.; Roso-Moliner, A.; Lozano, D. (Frontiers in Sports and Active Living, 2023)
Introduction: Padel's global growth highlights its technical complexity. The first publications focus on the physical aspects of padel, using methods that evaluate players' endurance, strength, speed, and range of motion, while the quantification of load, using internal and external indicators, is crucial for performance optimization, whilst taking into account athletes' profiles and levels. Therefore, the objective entailed analyzing the scientific literature about the conditional demands in competition within padel players from different levels.Methods: Data was collected from various databases and after the selection process, the information was analyzed in mini review.Results: The mini review shows that the conditional demands are categorized into internal and external load to try to obtain reference values that may define the demands of padel based on the competitive level and sex. Regarding the internal load, the heart rate (HR)% of the padel players from different levels is around 70-80% of the HR Max. Regarding the external load, in female´s categories, a greater number of strokes are made per point which entails a longer duration in the points.Conclusions: Padel research usually analyses physical demands using internal and external loading. HR% values (70-80% HR Max) are consistent across studies. There is variation between variables such as strokes per point, and contextual factors affect the metrics. Further exploration is vital to obtain comprehensive benchmarks and understand the demands of this sport.